Blind perceptual quality assessment method for DCT-based encoded images - Brandão, T.; Queluz, M. P. (15th European Signal Processing Conference, EUSIPCO 2007, 2007)
This paper describes a technique whose purpose is to estimate the perceptual quality of DCT-based encoded images, without requiring the original data. To achieve this objective, a watermark is embedded in the DCT domain using a non-uniform quantization scheme. At the receiver side, the original DCT coefficients data distribution is estimated using a maximum likelihood approach. These distributions and the extracted watermark are then combined to estimate the error between reference and distorted DCT coefficients. This error is perceptually weighted, using a DCT domain perceptual model, allowing to blindly score the quality of the received media. Results have shown the effectiveness of the proposed algorithm when scoring the quality of images subject to lossy compression.